PEMBERDAYAAN EKONOMI UMAT MELALUI KEARIFAN LOKAL - Mahmuda Mulia Muhammad (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2022)
Abstract Indonesia has good potential that is contained in the soil, above the ground, in the air and in the water that can be used to empower the people's economy. In addition, Indonesia consists of approximately 1,340 ethnic groups with different customs. This research was conducted based on a literature study with various references to journals and books as well as some of the best and most updated articles. if managed properly to empower the people's economy, then Indonesia can have unparalleled economic power. To achieve these goals, several things are needed in economic development such as: an Islamic economic system, building an entrepreneurial spirit, community unity, government policies and awareness of zakat and its management. And the most important thing is to explore the local potentials of each region, because local wisdom can function as a resource, competitiveness and performance lever. Keywords: Empowerment, People's Economy, Local Wisdom